Central obesity is more strongly associated with vertebral fractures than general obesity: a cross-sectional study - Yen-Huai Lin; Michael Mu Huo Teng (BMC Geriatrics)
Abstract Background Both general and central obesity have been linked to vertebral fractures; however, their specific effects on vertebral fractures have not been directly compared. This study aimed to investigate the associations between measures of general and central obesity and vertebral fractures. Methods This cross-sectional study of 1,011 postmenopausal women used dual-energy X-ray absorptiometry to measure bone density and body composition. Bone quality was assessed using the trabecular bone score. General obesity was evaluated using body mass index and body fat percentage, whereas central obesity was measured using waist circumference, waist-hip ratio, and android-gynoid ratio. Vertebral fractures were determined by retrospectively reviewing medical records, and only fractures confirmed by radiological reports were included. Results Obesity indices, including body mass index, body fat percentage, waist circumference, and android-gynoid ratio, were positively associated with bone density but negatively associated with trabecular bone score. General obesity, based on body fat percentage, was associated with vertebral fractures, whereas general obesity measured using body mass index was not. Central obesity assessed using waist circumference, waist-hip ratio, and android-gynoid ratio, was associated with vertebral fractures. Furthermore, among the different combinations of general and central obesity, central obesity measured by waist circumference and waist-hip ratio was still associated with vertebral fractures, irrespective of general obesity. Conclusions Central obesity was more strongly associated with vertebral fractures than general obesity in postmenopausal women. Therefore, developing and implementing measures to prevent central obesity are recommended.